Dual Gm-APD Polarization Lidar to Acquire the Depth Image of Shallow Semitransparent Media With a Wide Laser Pulse - Lu Xu; Xu Yang; Long Wu; Chenfei Jin; Yijia Zhang (IEEE Photonics Journal)
A polarization lidar with dual Geiger-mode avalanche photodiodes (Gm-APDs) is designed to obtain the high-precision depth image of shallow semitransparent media by using a wide laser pulse. The first surface of the semitransparent media is smooth and can nearly preserve the incident polarization, whereas the second surface is rough and can depolarize the incident polarization. A polarization splitting prism is utilized to separate the two echo signals, which will be detected by dual Gm-APDs. It gives the ability to obtain the extremely shallow depth independent of laser pulse width and dead time of Gm-APD. The theory of laser polarization transmission of dual Gm-APD polarization lidar is analyzed. Signal restoration & center-of-mass algorithm method is used to restrain the range walk error and obtain high range precision. The depth image of shallow semitransparent media with a thickness and distance of 10 cm and 6 m, respectively, is obtained in the experiment with a range precision of 1.1 cm. An experiment of real shallow water layer with different depth features is also performed to verify the result.